Pengaruh Penggunaan Metode Pembelajaran Discovery Learning Berbasis Media Quiz terhadap Hasil Belajar Siswa di SMA Negeri 1 Maros - Ahmad Ahmad; Apriadi Apriadi; Harmansyah Harmansyah; Munirah Munirah; Nasir Nasir; La Ode Reski Akuarta (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to improve student learning outcomes in Informatics subjects by using the Discovery Learning learning model in office application integration material in class X.10 UPT SMA Negeri 1 Maros. This research is classroom action research which has been carried out in 2 cycles. The subjects taken in this research were all students in class X.10 UPT SMA Negeri 1 Maros for the 2023/2024 academic year. The data collection technique in this research is (1). Observation, (2). Documentation, (3). Test. Based on the research results, it can be concluded that Discovery Learning is effectively used in Informatics material, this was shown in cycle 1, the presentation of student learning completeness was 36.8%, and in the second cycle it increased to 82.4%. The activities of students and teachers are also based on the results of observations and the model used in research, namely Discovery Learning, which is at an effective level given to students.